Hipolito Unanue in the Peruvian numismatics - Álvarez, Ricardo (2005)
Numismatics is the branch of History that studies coins, medals, decorations, paper money and related subjects through which we learn on the historic events of nations. Our country is doubtless one of the Latin American nations with the greatest traditions on the subject and some of our most illustrious figures are recalled through these small objects. Jose Hipolito Unanue is, along with Cayetano Heredia and Daniel Carrion, one of the most genuine representatives of the nation’s medical tradition. However, unlike the others, he was involved in politics and other sciences, giving him a dimension beyond the medical sphere. In this respect, numismatics has contributed to spread his image throughout the most remote parts of the world, allowing his face to be known by people who know nothing of our culture or even our language; yet, they can recognize him on a piece of paper or a metal disc. In spite of this, none of the research on Unanue has referred to his presence in numismatics, a gap that we hope to close by this article.